Risk factors for coronary calcification in older subjects The Rotterdam Coronary Calcification Study - OEI, Hok-Hay S; VLIEGENTHART, Rozemarijn; HOFMAN, Albert; OUDKERK, Matthijs; WITTEMAN, Jacqueline C. M (European heart journal, 2004)
We examined associations between cardiovascular risk factors and coronary calcification assessed by electron-beam tomography (EBT) in an unselected population of older subjects. The Rotterdam Coronary Calcification Study is a population-based study in subjects > =55 years. Participants underwent EBT scanning. Coronary calcification was quantified according to the Agatston score. Cardiovascular risk factors were assessed 7 years before and concurrently to scanning. We used the first 2013 participants for the present analyses. Risk factors assessed 7 years before scanning were strongly associated with calcium score. Associations with blood pressure and cholesterol attenuated when measured concurrently to scanning. Although the number of risk factors was strongly associated with a high calcium score in asymptomatic subjects, 29% of the men and 15% of the women without risk factors had a high calcium score. This population-based study in older subjects shows that cardiovascular risk factors are associated with coronary calcification. Associations were stronger for risk factors measured at earlier age. Almost 30% of the men and 15% of the women without risk factors had extensive coronary calcification.